Assessing the implementation of a mobile App-based electronic health record: A mixed-method study from South India - D M Shilpa; Poonam Ramesh Naik; Hemant Deepak Shewade; H Sudarshan (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Government of India recognizes the use of "information, communication, and technology" in the provision of comprehensive primary healthcare. In 2014-2015, Karuna Trust, a nongovernmental organization, Bengaluru, India, introduced an electronic health record (EHR) innovation, namely "Comprehensive Public Health Management" application (CPHM App). Data could be entered in an offline mode followed by syncing with cloud. The CPHM App was piloted in primary health center (PHC) Gumballi, in Karnataka, with focus on household survey and maternal and child health (MCH) services. OBJECTIVES: To compare the consistency of selected MCH process indicators for Health Management Information System [HMIS] available from paper-based records and those generated through the CPHM App (2016-2017). We also explored the implementation enablers, barriers, and suggested solutions from the user perspective. METHODS: A sequential mixed-method study design was followed. Quantitative phase involved aggregate data analysis looking into the consistency of selected MCH process indicators available from paper-based records and those generated through the CPHM App (2016-2017) followed by thematic analysis of in-depth interviews of healthcare providers. Consistency was defined as a percentage where the numerator was the HMIS-related process indicator data from CPHM App and denominator was the data from paper-based records. RESULTS: Three out of 12 selected MCH indicators had consistency of> 80%. The quarterly consistency reduced over the 2 years. Dual burden of entry and regular monitoring of paper-based records by district health and family welfare department were the reasons why more importance was given to entry in paper-based records. Ability to generate aggregate indicators with CPHM App, easy to use and retrieve data in the field, and reminder facility for planned health activities were some of the factors facilitating CPHM implementation. The key barriers were limited technical expertise and support from the technical team and no internet connectivity in the field and traveling to PHC to sync the data. Provision of real-time technical support and availability of data connectivity in the field were some of the solutions suggested. CONCLUSION: There should be a minimum of 1-2 years of simultaneous use of EHR and paper-based records after which one must shift to EHR.